Pembinaan Hukum Bagi Perusahaan Terhadap Pencemaran Lingkungan di Sektor Pertanian Guna Membangun Ketaatan Dan Kepedulian Lingkungan - Saptaning Ruju Paminto; Raden Mega Junia; Neng Diana; Nurul Aini; Eneng Rika; Yeli Yana (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research discusses the impact of environmental pollution from agricultural activities on the environment and society, as well as the legal responsibilities of companies in addressing such issues. Various types of environmental pollution common in the agricultural sector are included, such as water, air, soil and genetic pollution. The legal basis governing corporate responsibility for environmental pollution in the agricultural sector is also explained in detail, including provisions in Law No. 32/2009 on Environmental Protection and Management. The negative impacts of environmental pollution on the environment and society are fully described, ranging from ecosystem damage to human health impacts. To address the problem, measures to control and manage waste generated by agricultural and industrial activities are necessary, including public education and awareness. The conclusion of this study highlights the importance of implementing environmentally friendly agricultural practices and complying with applicable environmental regulations and laws to reduce the negative impacts of agricultural activities on the environment and society.